(untitled) (PANGEEA, 2025)
The relation between geology and mining is perfect symbiosis between a natural science and an engineering. Geological knowledge has been exercised from the very dawn of mankind, when first information on stones and minerals was gained. The Neolithic man has exploited silex, volcanic glass – the obsidian – that could be easily chipped, yielding nice and sharp, yet fragile tools. It is obvious that various hard and nicely colored minerals such as agate, charneol, turquoise, hematite, etc. could not pass unobserved, and the primitive man extensively used them as adornments. Later on, during the last two thousand years BC, primitive miners have explored and extracted metallic ores, firstly copper, then bronze and iron.